Formation of rutile (Cr, Ta, Ti)O2 oxides during oxidation of refractory high entropy alloys in Ta-Mo-Cr-Ti-Al system. (February 2023) - Schellert, S.; Weber, M.; Christ, H.J.; Wiktor, C.; Butz, B.; Galetz, M.C.; Laube, S.; Kauffmann, A.; Heilmaier, M.; Gorr, B.
Abstract: The chemical identity of rutile oxides formed during oxidation of alloys with different Ti content within the Ta-Mo-Cr-Ti-Al system at 1200 °C for 24 h was determined. Rutile-type oxide (Cr, Ta, Ti)O2 was observed on 20Ta20Mo20Cr20Ti20Al and 67.5(TaMoCr)10Ti22.5Al (at%). Based on the experimental results, the valence states of Cr, Ta and Ti were unequivocally determined. Higher concentrations of Ti in (Cr, Ta, Ti)O2 lead to the formation of thinner oxide scales and zones of internal corrosion. It is concluded that the occupation of higher-valent Ti 4+ cations on the Cr 3+ sub-lattice reduces the oxygen vacancy concentration and thus improves the oxidation behavior of n-type conducting (Cr, Ta, Ti)O2 -forming alloys. Highlights: Cation oxidation states of (Cr, Ta, Ti)O2, formed on alloys were determined by electron energy-loss spectroscopy. The protective properties of rutile (Cr, Ta, Ti)O2 are discussed based on the Wagner-Hauffe valence approach. A map of the lattice parameters of various transition metal-based rutile oxides is provided.